Kontribusi Ilmu Manajemen dalam Pengembangan Customer Relationship Management (CRM) - Ambar Lukitaningsih (Universitas Proklamasi 45 Yogyakarta, 2012)
Often found, that not all companies or businesses offering a product that they sell to realize the importance of a service to consumers. This could happen due to the many aspects of customer satisfaction, or products sold is a superior product or a great demand by consumers, so companies do not have anxiety or fear of abandonment by consumers. This paper attempts to reveal how management science has contributed to the marketing management in this system of CRM (Customer Relationship Management), which can be used by businesses to determine how these measures or ways to serve consumers, so that consumers feel satisfied, even become loyal customers and this will positively impact the company’s survival. CRM (Customer Relationship Management) which is a customer relationship management company is required to conduct a business or a strategy to serve customers well. CRM role here is not limited to customer satisfaction, but even further customers can continue to purchase products and or services that companies offer, so that with the implementation of CRM, the company can serve customers well and maintain customer loyalty. With the CRM is an evidence that the effect of the development of management science now filed under social sciences is very strong, which was initially characterized by the approach of a strong math and engineering. Until now, the influence of the more powerful approach, although the contribution of other social sciences also increasing. The condition makes multisources management as a hybrid science becomes stronger and attracts many people to learn and even more so of great benefit. The tendency of the environment to be hyper-competitive economy, the role of science greater getting out of a variety of problems or crises.